2010
DOI: 10.1002/app.32687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(epichlorohydrin) on the thermal and mechanical properties of poly(vinyl chloride)

Abstract: Five kinds of polyepichlorohydrin (PECH) of different molecular weights were synthesized and characterized by gel permeation chromatography (GPC). Mechanical blending was used to mix PECH and poly(vinyl chloride) (PVC) together. The blends of different PVC/ PECH ratios were characterized by thermogravimetric analysis (TGA), tensile tests, differential scanning calorimetry (DSC), and dynamic mechanical analysis (DMA). TGA results show the thermal stability of PVC/PECH blends is desirable. Tensile tests indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Scheme S1 in SI). The formation of an EP oligomer agrees with the lower decomposition temperature of CLE-0.5 and corresponds to a thermal event observed for an EP-based homopolymer [46].…”
Section: Ftir Spectroscopy Resultssupporting
confidence: 81%
“…Scheme S1 in SI). The formation of an EP oligomer agrees with the lower decomposition temperature of CLE-0.5 and corresponds to a thermal event observed for an EP-based homopolymer [46].…”
Section: Ftir Spectroscopy Resultssupporting
confidence: 81%
“…Although structures of the PVC and ECO are somewhat similar, but there is a miscibility range for the blends composed of these components. Ren et al investigated different properties of the PVC/poly(epichlorohydrin) (with M w = 2000–4000 g/mol) blends and observed that addition of more than 20 wt% of poly(epichlorohydrin) results in phase separation. In addition, as molecular weight of the rubber increases, compatibility between phases decreases.…”
Section: Resultsmentioning
confidence: 99%
“…3). Tg values were reported in the literatures for homo PECH and homo PMMA as − 43 °C [36] and 105 °C [37], respectively. Tg value of the comb-type graft copolymer changed to the value which was less than the value of PMMA because of PECH segment.…”
Section: Synthesis Of Poly(ech-g-mma) Comb-type Graft Copolymers By "mentioning
confidence: 99%